The Effect of Competence and Work Culture on Employee Performance Through Employee Commitment Bkn Regional Office XII Pekanbaru - Hasibuan, Agnes Rahmawati; Zulfadil, Zulfadil; Widayatsari, Any (Indonesian Journal of Economics, Social, and Humanities, 2025)
The purpose of this study was to ascertain and examine the impact of work culture and competency on employee commitment, among other goals. to ascertain and examine how employee performance is impacted by competence and workplace culture. to ascertain and examine how employee commitment affects worker performance. In order to ascertain and examine how employee engagement and work culture impact performance. In this study, the population was 102 employees of Regional Office XII BKN Pekanbaru. This research used a saturated sample method. The data used in this study are primary data and secondary data, while the data collection technique uses a questionnaire. The data analysisculture affect commitment. Competence and work culture affect employee performance. Commitment has a significant effect on employee performance. Competence has a significant effect on employee performance through commitment. This means that an employee's abilities, skills, and knowledge (competence) have an effect on their performance, and this impact occurs through their level of commitment to work or organization. Work culture has a significant effect on employee performance through commitment. This means that a positive and supportive work culture will increase employee commitment to the organization and their work.